Labor income risk and households' risky asset holdings. Issue 2 (6th June 2016) - Becker, Gideon; Dimpfl, Thomas
Abstract : Purpose: Financial theory suggests that with increasing labor income risk, the reluctance of households to hold stocks increases. Therefore, this paper aims to investigate the determinants of a household's decision on whether to invest in risky financial assets. Design/methodology/approach: Income risk is measured as the observed variation of household income over a five-year period. The authors use both the time and the cross-sectional dimension of the German socio-economic panel to control for unobserved heterogeneity. Findings: The authors find that indeed higher variation, i.e. higher income risk, reduces the propensity to invest in risky assets. However, when controlling for household heterogeneity, as well as subjective measures of a household's financial situation (income satisfaction, worries about financial situation), the impact of observed labor income variation vanishes. It is therefore concluded that in particular the perception of investment risk and of the riskiness of the environment determines the investment decision to a great extent. Originality/value: The paper contributes to a better understanding of a household's investment decision-making process. To the best of the authors' knowledge, it is the first to fully exploit the panel structure of the data to control for unobserved heterogeneity which leads to novel conclusions with respect to the effect of labor income.